EMPLOYEES AND COMMUNITY MEMBERS’ RATINGS OF ETHICAL PRACTICES BY LARGE SCALE BUSINESS ORGANIZATIONS IN CROSS RIVER STATE. - Eunice Ngozi, Ajuluchukwu,; Agnes Lawrence, Okute, (International Journal of Psychosocial Rehabilitation, 2020)
This study determined employees and community members’ ratings of the extent of ethical practices by large-scale business organizations in Cross River State. The extent of ethical marketing practices and ethical labor practices was studied. Two research questions guided the study while two hypotheses were tested at a 0.05 level of significance. The study was carried out in the 18 local government areas in the state. The survey research design was used for the research. Two sets of questionnaires were used for data collection. The instruments were validated by three experts. The reliability of the instruments was determined by means of the split-half reliability technique. The reliability coefficient of the questionnaires was determined using Pearson product-moment correlation analysis. The reliability coefficient of questionnaire A is 0.85, while that of questionnaire B is 0.82. The population of the study is 2241. This population included 578 community members in the state and 1663 employees from the six organizations studied. The sample for the study is 466. This comprised 216 community members and 250 employees. The sampling technique used was the three-stage multi-stage sample method. Data collected were analyzed using weighted mean scores for the research questions, one-way analysis of variance for hypothesis 1, and z-test statistics for hypothesis 2. The findings from the study revealed that the large-scale business organizations in Cross River State practice ethical marketing practices and ethical labor practices to a small extent. Some recommendations were made, which included that business organizations should sell acceptable products and treat customers and staff with respect instead of giving importance only to those areas where they have material interest.